2022
DOI: 10.5114/hivar.2022.112758
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis and predictors of mortality for adult HIV/AIDS patients following antiretroviral therapy in Mizan-Tepi University Teaching Hospital, Southwest Ethiopia: a retrospective cohort study

Abstract: Introduction: Acquired immune deficiency syndrome (AIDS) is a medical condition caused by human immunodeficiency virus (HIV), and has been the major concern worldwide. Despite antiretroviral treatment (ART) treatment showing significant clinical importance by meeting the goal of therapy, there is still a number of deaths due to socio-economic, demographic, and health-related factors. Therefore, this study was aimed to investigate the survival status and predictors of mortality for adult HIV-positive patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Acquired immune deficiency syndrome (AIDS) is currently one of the serious public health challenges worldwide [1]. AIDS is defined as the last stage of the disease that deteriorates immune system and makes the patient susceptible to opportunistic infections [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acquired immune deficiency syndrome (AIDS) is currently one of the serious public health challenges worldwide [1]. AIDS is defined as the last stage of the disease that deteriorates immune system and makes the patient susceptible to opportunistic infections [2].…”
Section: Introductionmentioning
confidence: 99%
“…AIDS is defined as the last stage of the disease that deteriorates immune system and makes the patient susceptible to opportunistic infections [2]. The disease is responsible for socio-economic crises, reduction in life expectancy, and devastating costs to health services [1]. The United Nations program on HIV/AIDS (UNAIDS) reported that in 2021, 37.7 million people were living with human immunodeficiency virus (HIV) worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation